Adverse effect of 2, 5PDC corrosion inhibitor on PEO coated magnesium. (November 2021) - Vaghefinazari, Bahram; Wang, Cheng; Mercier, Dimitri; Mei, Di; Seyeux, Antoine; Marcus, Philippe; Blawert, Carsten; Lamaka, Sviatlana V.; Zheludkevich, Mikhail L.
Abstract: Besides their noteworthy tribological and corrosion protection properties, Plasma Electrolytic Oxidation (PEO) coatings feature a porous microstructure that is able to host corrosion inhibitors. This study reveals that although 2, 5pyridindicarboxylate (2, 5PDC) shows a remarkable corrosion inhibition effect for bare AZ21 Mg alloy, it can extensively deteriorate a PEO coating on the same Mg substrate, resulting in an overall accelerated failure of the PEO-coated AZ21 alloy. The deteriorative behavior of 2, 5PDC towards PEO-coated AZ21 is explained based on the characterization of the bare and PEO-coated AZ21 exposed to the NaCl electrolyte with and without inhibitor using EIS, SEM, STEM and ToF-SIMS. Highlights: 2, 5PDC could effectively inhibit the corrosion of AZ21 in 3.5 wt% NaCl. 2, 5PDC could accelerate the degradation of AZ21 coated with the phosphate-based PEO. The inhibition/adverse effect of 2, 5PDC on bare/coated AZ21 is intensified with its concentration. Formation of a soluble complex between Mg 2+ and 2, 5PDC destabilizes the PEO layer. Formation of a relatively thick corrosion layer on AZ21 accelerates the failure of PEO coating.